Fatores de risco para infecção pelos vírus da diarreia viral e rinotraqueíte infecciosa bovina no Sítio Histórico e Patrimônio Cultural Kalunga - Dias, Juliana Moraes (2016)
The research consisted of evaluating the frequency of seropositive animals for viral diarrhea and infectious bovine rhinotracheitis and determining correlations with environmental, social and health characteristics of the region. The study was carried out in herds of the Kalunga’s Historical and Cultural Heritage Site, located in the north of the state of Goiás, it is an area of Cerrado with native pastures and few formed areas. Blood samples were collected from 2,612 cattle of different breeds and age groups, male and female, corresponding to 79 predominantly beef cattle. During sample collection, an epidemiological questionnaire was applied to investigate factors that could be associated with infections. The samples were submitted by the ELISA method, to detect antibodies against BVD and IBR. The average frequency of seropositive herds was 88.6% for BVD and 97% for IBR, the individual positive serology corresponded to 17.8% for BVD and 45.5% for IBR. There was a significant difference (p <0.05) between the regions and age group for both diseases. The environmental variables associated with the frequency of BVD were: level of precipitation and maximum temperature of the hottest month of the year, and for IBR: INDV and temperature seasonality. Contact with other species of animals, reproductive problems, presence of wetland, use of cattle as the main source of income, educational level of the producer and marital status were correlated risk factors for the occurrence of BVD and IBR.